Targeting Receptors, Transporters and Site of Absorption to Improve Oral Drug Delivery - J.H. Hamman; P.H. Demana; E.I. Olivier (AboutScience Srl, 2007)
Although the oral route of drug administration is the most acceptable way of self-medication with a high degree of patient compliance, the intestinal absorption of many drugs is severely hampered by different biological barriers. These barriers comprise of biochemical and physical components. The biochemical barrier includes enzymatic degradation in the gastrointestinal lumen, brush border and in the cytoplasm of the epithelial cells as well as efflux transporters that pump drug molecules from inside the epithelial cell back to the gastrointestinal lumen. The physical barrier consists of the epithelial cell membranes, tight junctions and mucus layer. Different strategies have been applied to improve the absorption of drugs after oral administration, which range from chemical modification of drug molecules and formulation technologies to the targeting of receptors, transporters and specialized cells such as the gut-associated lymphoid tissues. This review focuses specifically on the targeting of receptor-mediated endocytosis, transporters and the absorption-site as methods of optimizing intestinal drug absorption. Intestinal epithelial cells express several nutrient transporters that can be targeted by modifying the drug molecule in such a way that it is recognized as a substrate. Receptor-mediated endocytosis is a transport mechanism that can be targeted for instance by linking a receptor substrate to the drug molecule of interest. Many formulation strategies exist for enhancing drug absorption of which one is to deliver drugs at a specific site in the gastrointestinal tract where optimum drug absorption takes place.